2005
DOI: 10.1215/s1152851705000256
|View full text |Cite
|
Sign up to set email alerts
|

Combined immunoradiotherapy induces long-term remission of CNS relapse of peripheral, diffuse, large-cell lymphoma after allogeneic stem cell transplantation: Case study

Abstract: Relapse of peripheral non-Hodgkin's lymphoma (NHL) in the central nervous system commonly has a poor prognosis. Graft-versus-leukemia effects (GvL) contribute substantially to eradication of hematological malignancies after allogeneic stem cell transplantation. Few data are available describing GvL activity within the brain. We report the case of a man allografted for peripheral NHL. On day +83 after transplantation a CNS relapse of the lymphoma occurred. The brain was irradiated with 44 Gy, anti-CD20 antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Unfortunately, a possible survival benefit with this strategy would be obscured by an elevated treatment-related mortality. In this scenario, a German case study on a patient allografted for systemic NHL with a favourable course has been reported [54]. On day þ83 after transplantation a CNS relapse of the lymphoma occurred.…”
Section: Allogeneic Stem-cell Transplantationmentioning
confidence: 99%
“…Unfortunately, a possible survival benefit with this strategy would be obscured by an elevated treatment-related mortality. In this scenario, a German case study on a patient allografted for systemic NHL with a favourable course has been reported [54]. On day þ83 after transplantation a CNS relapse of the lymphoma occurred.…”
Section: Allogeneic Stem-cell Transplantationmentioning
confidence: 99%
“…Furthermore, the successful treatment by allogeneic BSCT of patients with isolated CNS relapse of acute leukemia has been published [21]. In a prior publication we reported the successful therapy of CNS-relapse of high-grade NHL with alloSCT, immunomodulation and irradiation [22]. The clinical and molecular remission of SMZL in this case strongly suggest contribution of GvL-effects, however, the relative short follow-up of three years allows no definite conclusion.…”
Section: Discussionmentioning
confidence: 86%
“…A comparable finding has also been reported in a patient with a cerebral relapse of high-grade malignant lymphoma after an allogeneic transplant. 3 To our knowledge, this is the first case of a vHCL that showed an intra-abdominal tumorous (chloroma-like) relapse after allogeneic transplantation. It has to be pointed out that this relapse occurred in the presence of a limited chronic GvHD.…”
mentioning
confidence: 75%